2019
DOI: 10.3390/w12010005
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Estimation from Major Physical Hydrology Components Using Artificial Neural Networks and Deep Learning

Abstract: Precise estimation of physical hydrology components including groundwater levels (GWLs) is a challenging task, especially in relatively non-contiguous watersheds. This study estimates GWLs with deep learning and artificial neural networks (ANNs), namely a multilayer perceptron (MLP), long short term memory (LSTM), and a convolutional neural network (CNN) with four different input variable combinations for two watersheds (Baltic River and Long Creek) in Prince Edward Island, Canada. Variables including stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…However, because of data normalization of the datasets, the RNNs used in the study were successfully converged without over and under fitting with approximately equal training and testing accuracies. Similar results were found in a study by Afzaal et al, [34] as no major effect of dropout was observed with normalized data. Therefore, all the RNNs used in this study were trained without introducing dropout in LSTM layers.…”
Section: Model Training and Tesing Evaluationsupporting
confidence: 92%
See 2 more Smart Citations
“…However, because of data normalization of the datasets, the RNNs used in the study were successfully converged without over and under fitting with approximately equal training and testing accuracies. Similar results were found in a study by Afzaal et al, [34] as no major effect of dropout was observed with normalized data. Therefore, all the RNNs used in this study were trained without introducing dropout in LSTM layers.…”
Section: Model Training and Tesing Evaluationsupporting
confidence: 92%
“…The root means square error (RMSE) and R 2 were used to evaluate the model effectiveness as these two evaluation parameters have been used in various studies to evaluate the neural networks predictive power [22,33,34]. Values of R 2 closer to 1 represented the models with higher predictive power.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This has raised concerns about groundwater sustainability, its responsible use, and saltwater intrusion in the system. A recent study by Afzaal et al [25] pointed out the lower groundwater levels than expected in the summer season as a consequence of pumping. This situation has created challenges for water resources managers to meet the supplemental irrigation demands of crops for their sustainable production.…”
Section: Introductionmentioning
confidence: 96%
“…The state of art DL capabilities have not yet been tested in hydrological modelling and there are only a few DL applications so far (Shen et al, 2018). Successful DL applications in hydrology include rainfall-runoff modelling (Hu et al, 2018;Fan et al, 2020;Xiang et al, 2020), soil moisture modelling (Xiaodong et al, 2016), precipitation forecasting (Kumar et al, 2019), groundwater estimation (Afzaal et al, 2019) and uncertainty estimation (Gude et al, 2020).…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%